MANFAAT PENDIDIKAN KESEHATAN REPOSISI DAN MINYAK KELAPA TERHADAP PENCEGAHAN DEKUBITUS - Amik Muladi,, Betty Sunaryanti, (Prosiding Seminar Nasional, 2014)
Background: The results Kurniawan(2009) demonstrate knowledge of the meaning of decubitus nurses 66.7%, 59% prevention purposes, and prevention of pressure sores 51.3%. The prevalence of pressure sores were reported in homes in the range of 12.9% to 19% (Potter andPerry., 2005). Suheri research results (2009) showed that thelength of stayin the occurrence of decubitus so reson patient immobilizati on decubitus sores 88.8% with an average length of stay on the fifth day oftreatment. Purpose: to determine the benefits of health education repositioning with coconutoil.Â Methods: This studyis aquantitati vestudy with Randomize Controlled Trial. Assessment ofpatients using the Norton scale assessment. Research will be held for 7days. Statistical testtouse thet-test.Â Referrals: The results wer every influential studyis the provision of health education to thecommunity about reposition ingcoupled with feeding coconut oil with p: 0.015, throughproceedings publications and text books.